Cooperative control of time-delay wind power grid-connected unit under actuator saturation based on Hamiltonian method - Wang, Gaoran; Sun, Weiwei; Ding, Lusong (International journal of electrical power & energy systems, 2023)
In large-scale wind power generation, wide area control is often employed to overcome power oscillation, but this can result in the appearance of time-delayed voltage, which is transmitted to the wind power grid-connected system as an input signal. Additionally, ensuring the security of multi-grid parallel connection requires limiting the amplitude of the input signal. To address these challenges, this paper investigates the cooperative control problem for time-delayed wind power grid-connected unit under actuator saturation constraints. A novel control strategy that combines passive control with synchronous control is proposed. The system is transformed into a Hamiltonian structure, and a passive controller is designed using the principle of interconnection and damping assignment passivity-based (IDA-PB) to ensure stability. Based on this, an output feedback synchronous controller is proposed to account for saturation when multiple grids are connected in parallel. Stability criteria are provided to ensure the asymptotic stability of each closed-loop system and synchronous stabilization of all systems. Finally, simulation results verify the effectiveness of the proposed control strategy. •A novel cooperative controller design method that integrates IDA-PB passive control and synchronous control is proposed.•The original IDA-PB passive controller design process is innovated by introducing the state feedback at the desired equilibrium point.•The LMI conditions that enable the entire unit to overcome the combined effects of input delay, state delay and actuator saturation are derived.